Education on the Benefits of Warm Water Consumption Prior to Nebulizer Therapy in Improving Airway Patency Among Asthma Patientsat Grandmed Hospital Lubuk Pakam - Simarmata, Juni Mariati; Angriawan, Angriawan; Juliardi, Fery; Simanjuntak, Elfrida (JURNAL PENGMAS KESTRA (JPK), 2025)
Asthma is a respiratory disorder characterized by inflammation, airway narrowing, and excessive mucus production, which leads to shortness of breath. A commonly applied therapy during acute asthma attacks is the use of a nebulizer, which delivers medication in the form of vapor inhaled directly into the airways. The effectiveness of nebulizer therapy is influenced by the physiological condition of the patient’s airway prior to the treatment. Warm water consumption has been shown to support respiratory function by maintaining mucosal hydration and softening mucus secretions. This community service program aimed to educate the public on the potential benefits of warm water consumption in enhancing the effectiveness of nebulizer therapy in relieving airway obstruction among asthma patients. The program was implemented with 25 participants, all of whom were asthma patients at Grandmed Hospital in Lubuk Pakam. The educational activity included delivering the intervention material, followed by interactive sessions such as Q & A and group discussions. Knowledge improvement was assessed by comparing post-test scores with pre-test scores. The results demonstrated a notable increase in participants’ knowledge, with an average score improvement of 34.1 points or 64.6%. Additionally, approximately 98% of participants reported that the educational session was beneficial and easy to understand. Participants showed improved comprehension of nebulizer mechanisms and recognized the importance of warm water intake prior to therapy. The educational intervention successfully enhanced participants understanding and encouraged the application of warm water consumption before nebulizer therapy, potentially leading to more effective treatment outcomes.